State and Trends of Carbon Pricing 2017 - World Bank (Washington, DC: World Bank, 2017)
Reflecting the growing momentum for carbon pricing worldwide, the 2017 edition of the State and Trends of Carbon Pricing targets the wide audience of public and private stakeholders engaged in carbon pricing design and implementation. This report also provides critical input for negotiators involved in the implementation of the Paris Agreement, particularly for the meeting of the Conference of the Parties (COP} 23 to be held in Bonn in November 2017.